Which is better to decompress the nerve roots in cervical radiculopathy:stretching or traction from foraminal opening position? - Mohamed Aly Hassan, Mahmoud; Farag Hanafy, Abeer; Hafez Hassan, Samiha; Mohamed Abdelmeged, Shaymaa; Mohamed Elhafez, Salam (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Cervical traction has long been used to relieve compression of nerve roots caused by intervertebral discs. Yet,there is lack of knowledge on comparing the effect of traction decompression with neck muscle stretching in patients with cervicalradiculopathy (CR). This study investigated the effect of different angles of decompression on the flexor carpi radialis H-reflex,Neck Disability Index (NDI), and pain level (determined with the visual analogue scale) in patients with CR and compared theresults with neck muscle stretching.Methods. Overall, 58 patients with CR were randomly assigned to 4 groups. Group A received a stretching protocol to thecervical musculature. Group B was treated with traction therapy from neutral position with rope angle 0°. Group C underwenttraction therapy from 30° lateral bending toward the side opposite to radiculopathy. Group D was managed with traction from15° flexion with 30° lateral bending to the side opposite to radiculopathy and 15° rotation toward the side of radiculopathy. Allparticipants were assessed before and after 6 weeks of treatment.Results. Mixed design MANOVA revealed that the H-reflex increased significantly (p < 0.05) after treatment in groups A, B,and D. However, it increased non-significantly in patients within group C. NDI and pain scores decreased significantly aftertreatment in all tested groups.Conclusions. Decompression traction from retracted neutral position with 0° rope angle and foraminal opening directions isas effective as stretching of ipsilateral neck muscles in enhancing nerve root decompression and reducing pain in patients with CR.
Keywords: stretching; cervical radiculopathy; traction decompression; H-reflex; Neck Disability Index